2019
DOI: 10.1016/j.jcol.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Local irrigation with silver nitrate, a non-surgical approach for persistent anal fistula

Abstract: Purpose  Treatment of persistent anal fistula implies a major challenge for surgeons, with risk of additional recurrence and potential continence impairment. We present a non-surgical treatment based on irrigation with silver nitrate 1% solution. Methods  This is a prospective study including patients with persistent anal fistula after surgery, who were treated with silver nitrate 1% solution irrigation from May 2015 to March 2017. Patients with evidence of abscess, presence of >1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Placer-Galán et al 12 treated recurrent anal fistula with silver nitrate solution and reported a complete healing rate of 44%, which correlates well with our current results. Tomasello et al 13 reported three cases treated with an Argentum-Quartz solution.…”
Section: Discussionsupporting
confidence: 91%
“…Placer-Galán et al 12 treated recurrent anal fistula with silver nitrate solution and reported a complete healing rate of 44%, which correlates well with our current results. Tomasello et al 13 reported three cases treated with an Argentum-Quartz solution.…”
Section: Discussionsupporting
confidence: 91%